Full embroidery designed electro-textile wearable tag antenna for WBAN application - Dawood, Bahaa Abbas; Khamas, Salam K.; Ismail, Alyani; Sali, Aduwati (MDPI, 2019)
A flexible and totally wearable textile antenna is proposed by embroidering the conductive threads into garments. A purely polyester substrate has been utilized, which provides a tag that can be easily integrated with the clothes. The proposed tag antenna is small with dimensions of 72 × 20 × 2.75 mm3 and offers an enhanced performance in terms of gain and stability when worn on different body locations. Experimental results demonstrate an improved impedance matching owing to the elasticity of the E-shaped inductive feeder. Close agreement has been achieved between the simulated and measured results.